Challenges of Christian Religious Education Teachers in Facing Era Society 5.0 - May (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
The teacher is one of the components of education and includes christian religious education that largely determines the success or failure of the aims of Christian religious education. A christian religious education teacher is a teacher who educates students, young and old about the christian faith, imitating Jesus Christ in daily life and in carrying out his teaching duties. One of the goals of christian religious education is to produce human beings who can live their faith responsibility in a pluralistic society. This research uses a qualitative approach with a literature study method. This research data collection technique is by the discussion regarding the challenges of christian religious education teachers in facing the era of society 5.0. The results of this research.